Кременецький ліцей у структурі навчальних закладів Другої Речі Посполитої - Крамар, Юрій Вікторович; Kramar, Jurii (My University, 2016)
У статті висвітлено діяльність одного з провідних навчальних закладів міжвоєнної Волині – Кременецького ліцею. Проаналізовано основні структурні підрозділи ліцею, досліджено національний склад його учнів і кадрове забезпечення викладацького складу. З’ясовано роль закладу як осередку польської культури на Волині.Kremenetski Liceum in the Structure of Educational Establishments in the Second Polish Repablic. The article lights up the activity of one of the leading educational establishment - Kremenetski liceum in the interwar Volyn. The structure of the lyceum is analysed, the national component of its students and skilled providing of teaching staff are investigated. Attention is paid to the forms of out-of-school leisure of students. It is illuminated the activity of scientifically-cultural establishments, that functioned in the component of Kremenetski lyceum - libraries, museum, Volyn research institute.
Kremenetski Liceum in the Structure of Educational Establishments in the Second Polish Repablic
Keywords: Волинь; міжвоєнний період; освітня система; ліцей; польська культура; Volyn; interwar period; educational system; lyceum; polish culture